Emerging role of PARP‐1 and PARthanatos in ischemic stroke. Issue 1 (28th July 2021) - Liu, Shuiqiao; Luo, Weibo; Wang, Yingfei
Abstract: Cell death is a key feature of neurological diseases, including stroke and neurodegenerative disorders. Studies in a variety of ischemic/hypoxic mouse models demonstrate that poly(ADP‐ribose) polymerase 1 (PARP‐1)‐dependent cell death, also named PARthanatos, plays a pivotal role in ischemic neuronal cell death and disease progress. PARthanatos has its unique triggers, processors, and executors that convey a highly orchestrated and programmed signaling cascade. In addition to its role in gene transcription, DNA damage repair, and energy homeostasis through PARylation of its various targets, PARP‐1 activation in neuron and glia attributes to brain damage following ischemia/reperfusion. Pharmacological inhibition or genetic deletion of PARP‐1 reduces infarct volume, eliminates inflammation, and improves recovery of neurological functions in stroke. Here, we reviewed the role of PARP‐1 and PARthanatos in stroke and their therapeutic potential. Abstract : We reviewed the multifaceted effects of poly(ADP‐ribose) polymerase 1 (PARP‐1) in stroke and its therapeutic potential. PARP‐1 hyperactivation leads to poly(ADP‐ribose) accumulation, which 1) enables nuclear–mitochondria cross talk and triggers PARP‐1‐dependent cell death (PARthanatos); 2) causes NAD + depletion and regulates metabolic reprogramming; 3) regulates ion homeostasis and aggravates calcium influx leading to a vicious cycle of excess calcium influx and excitotoxicity; and 4) induces neuroinflammation by activating transcription factors and their downstream gene expression.